Comparative efficacy of trastuzumab deruxtecan versus guideline-recommended treatments for 2L+ unresectable locally advanced or metastatic HER2-mutant non-small cell lung cancer: a systematic review and indirect treatment comparison - Cappuzzo, Federico; Zhang, Lirong; Dunton, Kyle; Dennis, Natalie; Le Nouveau, Pauline; Nevière, Agathe; Gauthier, Aline (Frontiers in Oncology, 2026)
IntroductionThe clinical benefit of trastuzumab deruxtecan (T-DXd 5.4mg/kg), the first approved HER2-directed therapy for patients with previously treated HER2-mutant (HER2m) non-small cell lung cancer (NSCLC), was demonstrated in the phase II DESTINY-Lung02 trial. This study evaluated the efficacy of T-DXd relative to other approved treatments, including immunotherapies, vascular endothelial growth factor inhibitors, and chemotherapies, for adult patients with unresectable locally advanced or metastatic HER2m non-squamous NSCLC whose disease had progressed following ≥1 systemic therapy.MethodsA systematic literature review was conducted through September 2020 and supplemented in 2023 to identify relevant clinical trials. Given the single-intervention design in DESTINY-Lung02, two external comparator arms (ECAs) were created using docetaxel from INTEREST and VITAL, to connect T-DXd to a broader evidence network. Hazard ratios for progression-free survival (PFS) and overall survival (OS), and odds ratios (ORs) for overall response rate (ORR) were estimated via network meta-analysis. Matching adjusted indirect comparisons (MAICs) were also conducted for PFS and OS.ResultsFourteen studies with nine different regimens were included in the analysis. T-DXd showed better efficacy than all comparators, with a 100% probability of being the best treatment for PFS, ≥59% for OS, and ≥80% for ORR. Notably better PFS improvements were observed on T-DXd across all comparisons, with hazard ratios (HRs) [95% CrI] varying from 0.15 [0.09, 0.26] versus pemetrexed to 0.33 [0.20, 0.56] versus paclitaxel + bevacizumab. A similar trend was noted for OS. Patients on T-DXd maintained superior OS benefit versus other available treatments, with a notable difference demonstrated over paclitaxel + bevacizumab (HR [95% CrI]: 0.54 [0.30, 0.97]). As for ORR, the highest rate was achieved by T-DXd (49%), with odds ratios ranging from 6.09 to 21.14, representing a multifold increase compared with other regimens. Consistent results were obtained between the two different ECAs and the alternative approach via pairwise MAICs.ConclusionThis ITC suggested that T-DXd was associated with a consistent and meaningful benefit in terms of PFS and favorable OS relative to relevant comparators. For HER2m metastatic NSCLC adults, this review supports that T-DXd may be the best treatment option in the second-line or later settings.